Entrevista: Fuentes Hist ´oricas del Perú. - Drinot, Paulo (Latin American Research Review, 2025)
Fuentes Hist ´oricas del Perú (FHP) has become an essential resource for historical research in the country. This initiative, led by students from Peruvian universities, represents a significant advance in the broader process of creating digital resources for historical research and the development of digital humanities in Peru. This interview, conducted in late 2023 by Paulo Drinot with Jair Miranda Tamayo, Erika Caballero Linán and Carlos Paredes Hernández, the three founders of FHP, provides an ˜ overview of FHP’s origins, characteristics, and objectives.